A case of pulmonary embolism with rare unusual presentation of syncope - Srivastava, Rajeev; Prasad, Avneesh; Bharadwaj, Shivum; Gupta, L C (Nepalese Heart Journal, 2018)
Presentation in pulmonary embolism may be variable and each patient should be thoroughly investigated including young patients. Other non-conventional presentation and risk factors should also be assessed. Appropriate management should be considered for this life threatening disease in hospital and follow up with anticoagulants is necessary for prevention of recurrences.